Minnesota One Health Antibiotic Stewardship Collaborative: A Reproducible Approach to Facilitate Antimicrobial Stewardship Progress. (16th December 2022) - Bollig, Emma R; Hirsch, Elizabeth B; Bueno, Irene; Lynfield, Ruth; Granick, Jennifer L; Gens, Krista D; Rashid, Ayesha; Harris, Kelly; Boeser, Kimberly; Beaudoin, Amanda L
Abstract: The Minnesota One Health Antibiotic Stewardship Collaborative (MOHASC) was launched in 2016 with the mission of providing a collaborative environment to promote judicious antibiotic use and antibiotic stewardship (AS) and to reduce the impact of antibiotic-resistant pathogens of human, animal, and environmental health importance. MOHASC goals include improving AS programs in healthcare and veterinary medicine, advancing understanding of environmental impacts of antibiotic use, and promoting a One Health (OH) approach to AS. These goals are accomplished through quarterly meetings of 4 work groups, field trips, collaborative research, an annual member meeting, and public education events. This novel OH approach has strengthened multidisciplinary relationships within Minnesota and led to procurement of funding to enhance AS initiatives beyond the Collaborative. This perspective serves as a blueprint for other jurisdictions, and we advocate for use of this reproducible OH strategy to facilitate broad AS goals. Abstract : We describe the history, structure, and activities of the Minnesota One Health Antibiotic Stewardship Collaborative, which provides a collaborative environment for professionals in human, animal, and environmental health to promote judicious antibiotic use and reduce the impact of antibiotic-resistant pathogens.